2016
DOI: 10.1088/0031-9155/61/21/n565
|View full text |Cite
|
Sign up to set email alerts
|

Range optimization for mono- and bi-energetic proton modulated arc therapy with pencil beam scanning

Abstract: The development of rotational proton therapy plans based on a pencil-beam-scanning (PBS) system has been limited, among several other factors, by the energy-switching time between layers, a system-dependent parameter that ranges between a fraction of a second and several seconds. We are investigating mono- and bi-energetic rotational proton modulated arc therapy (PMAT) solutions that would not be affected by long energy switching times. In this context, a systematic selection of the optimal proton energy for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Besides, a recent study in prostate cancer has found that it is not possible to simultaneously meet the tumor and rectal constrains for both physical and variable RBE‐weighted dose, the latter being estimated based on in vitro cell survival data. In fact, other groups have decided to avoid the sometimes controversial concept of proton RBE completely and have tackled this problem by performing the optimization directly on LET distributions or proposing new beam orientations or treatment modalities …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a recent study in prostate cancer has found that it is not possible to simultaneously meet the tumor and rectal constrains for both physical and variable RBE‐weighted dose, the latter being estimated based on in vitro cell survival data. In fact, other groups have decided to avoid the sometimes controversial concept of proton RBE completely and have tackled this problem by performing the optimization directly on LET distributions or proposing new beam orientations or treatment modalities …”
Section: Introductionmentioning
confidence: 99%
“…In fact, other groups have decided to avoid the sometimes controversial concept of proton RBE completely and have tackled this problem by performing the optimization directly on LET distributions [35][36][37][38][39] or proposing new beam orientations or treatment modalities. [40][41][42] Our proposed solution is the use of a mixed RBE model (MultiRBE) for plan optimization, where a uniform RBE is used in the target contours to ensure an adequate tumor coverage in terms of physical dose, but a variable RBE is used elsewhere. This solution incorporates the benefits of both approaches: it produces a quantifiable, numeric RBE quantity that can be used for weighting of physical dose, but it also ensures appropriate coverage of the target with a flat physical dose distribution.…”
Section: Introductionmentioning
confidence: 99%
“…After being used successfully in several research projects, FoCa and matRad were utilized for teaching purposes in two courses during academic year 2016/2017 at the our University: Nuclear Physics Applied to Medicine (from the MSc in Nuclear Physics) and Hadron therapy (from the Summer School on Advanced Topics in Medical Physics), with a total of over 60 students. The objective of the learning experiences was the familiarization of the students with treatment planning techniques, pencil beam modeling, and radiobiology applied to treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Beam number and beam angle selection will also be important considerations: wide "hinge-angles" between beams offer greater scope for LET optimisation and even proton arc-based solutions have been proposed. 4 But ultimately, RBE is more than an end-of-range problem that can be easily mitigated by incorporating physics-based surrogates into treatment plan optimisation. Even after physics-based mitigation, RBE introduces considerable biological uncertainty into predictions of treatment response.…”
mentioning
confidence: 99%